Associations Between Defence-Style, Eating Disorder Symptoms, and Quality of Life in Community Sample of Women: A Longitudinal Exploratory Study - Aouad, Phillip; Hay, Phillipa; Foroughi, Nasim; Cosh, Suzanne M.; Mannan, Haider (Frontiers in Psychology, 2021)
Background and Aim: Eating Disorders (EDs) impact an estimated 15% of the global population and are linked to maladaptive defence-styles (coping strategies) and poorer mental health outcomes. Defence-styles have been grouped into immature, neurotic, and mature behaviours. Studies have yet to examine all three defence-styles in ED symptomatic individuals over an extended period of time. The current study aimed to investigate using converse analysis the relationships between defence-style and ED outcomes over a 5-year period. Methods: Participants (n=216, mean age 33 years) were recruited through the Women’s Eating and Health Literacy study, with the current study examining a five-year period of two waves (year-4 and year-9). The current study tested associations over time between eating pathology (EDE-Q), psychological distress (K10), mental and physical health related quality of life (M/PHRQoL, SF-12), and defence-style (DSQ-40). Results: Mature, immature and neurotic defence-styles did not significantly change over five years. Over the same period, only PHRQoL significantly predicted mature defence-styles having positive effect. Both MHRQoL and PHRQoL significantly predicted immature defence-styles having positive and negative effects respectively. Psychological distress, PHRQoL and weight concern significantly predicted neurotic defence-styles having positive effects except for psychological distress. PHRQoL, MHRQoL, restraint and eating concern significantly predicted overall eating pathology having positive effects except for PHRQoL and MHRQoL. Conversely, among the defence-style variables, over five years, both immature and neurotic defence-styles significantly predicted psychological distress having positive effects, immature and mature defence-styles significantly predicted MHRQoL having negative and positive effects respectively, while only immature defence-styles significantly predicted overall eating pathology having positive effect. Conclusions: The results of the current study suggest that immaturity and neuroticism but not maturity were the defence-style variables predicting psychological distress over a five-year period while conversely psychological distress predicted only neurotic defence styles. The findings of the current study may suggest that without intervention, mature, immature and neurotic defence-styles may largely remain immutable to significant shifts over time. Limitations in the current study included limited demographic representation. The current study is anticipated to generate considerations into treatments that could strengthen defence-styles in individuals with increased eating pathology.